Multi-banded pumice in the Campo de la Piedra Pómez rhyolitic ignimbrite (Southern Puna plateau): Pre-eruptive physical and chemical interactions between mafic and rhyolitic melts. (August 2020) - Bardelli, L.; Arnosio, M.; Báez, W.; Suzaño, N.; Becchio, R.; Viramonte, J.; Bustos, E.; Bertea, E.
Abstract: The rhyolitic Campo de la Piedra Pómez ignimbrite crops out in the Southern Puna of NW Argentina and it is related to the youngest caldera-complex (Cerro Blanco caldera complex) of the Central Andes (73 - 4 kyr). The presence of rhyolitic pumice and mafic enclaves with different compositional and textural features, which variability can be observed within a single juvenile clast (multiple-banded pumice), characterized these deposits. The enclaves are associated with hybrid (trachydacitic) pumice and sporadic remnants of rhyolitic material included in the trachydacite. To unravel the possible role of the mafic recharge as eruption trigger, the occurrence of mixing events and the mechanisms of enclave formation, we studied the enclaves and silicic pumice material (petrography, whole rock analyses, mineral and glass chemistry) to decipher the magmatic interaction between the host rhyolitic melt and the enclave-forming magmas. Results allowed recognizing two main mafic recharge events. During the first episode, the mixing of the rhyolite with the injecting magma generated sporadic dacitic products. Mixing was favored by the relatively high temperature of both the injecting magma and the rhyolitic melt, as revealed by clinopyroxene-liquid, plagioclase-liquid and two-pyroxene geothermometers (≥875 °C). The second mafic recharge event involved magma that remained confined at the bottom of the reservoir and crystallized with differential cooling rates. At the interface with the silicic host, the magma generated sub-millimetric mineral assemblage in which amphibole has normally zoned rims. Differently, within the body of the mafic intrusion, crystallization proceeded with a lower undercooling degree, generating a coarser crystalline assemblage in which amphibole crystals do not display zoning. The convergence of different thermobarometric models (applied to the rhyolite, trachydacite, and enclaves) suggests that these magmas interacted at a crustal depth of ca. 2.7 Kbar, here interpreted as the base of the Campo de la Piedra Pómez rhyolitic reservoir (~10 Km b.s.l.). A time lapse occurred between the last mafic recharge and the eruptive events, where the felsic magma cooled down to ~800 °C and the amphibole re-equilibration took place. Highlights: Pleistocene rhyolitic ignimbrite with multi-banded pumice clasts (mafic enclaves). Chemical hybridization of rhyolite and basalt to form dacitic rocks. Enclave amphibole zoning reflecting re-equilibration in the rhyolitic reservoir. Pre-eruptive cooling stage of rhyolitic melt to 800 °C at a depth of 2.6 Kbar.